Virtual Reality–Based Biofeedback and Guided Meditation in Rheumatology: A Pilot Study. Issue 10 (11th November 2019) - Venuturupalli, R. Swamy; Chu, Timothy; Vicari, Marcus; Kumar, Amit; Fortune, Natalie; Spielberg, Ben
Abstract : Objective: As technology continues to improve, it plays an increasingly vital role in the practice of medicine. This study aimed to assess the feasibility of the implementation of virtual reality (VR) in a rheumatology clinic as a platform to administer guided meditation and biofeedback as a means of reducing chronic pain. Methods: Twenty participants were recruited from a rheumatology clinic. These participants included adults with physician‐diagnosed autoimmune disorders who were on a stable regimen of medication and had a score of at least 5 on the pain Visual Analog Scale (VAS) for a minimum of 4 days during the prior 30 days. VAS, part of most composite outcome measurements in rheumatology, is an instrument used to assess pain that consists of a straight line with the endpoints ranging from "no pain at all" and "pain as bad as it could be." Patients were randomized into two groups that differed in the order in which they experienced the two VR modules. One module consisted of a guided meditation (GM) environment, whereas the other module consisted of a respiratory biofeedback (BFD) environment. Data on pain and anxiety levels were gathered before, during, and after the two modules. Results: The three most common diagnoses among participants were rheumatoid arthiritis (RA), lupus, and fibromyalgia. There was a significant reduction in VAS scores after BFD and GM ( P values = 0.01 and 0.04, respectively). There was a significant reduction in Facial Anxiety Scale after the GM compared with the BFD ( P values = 0.02 and 0.08, respectively). Conclusion: This novel study demonstrated that VR could be a feasible solution for the management of pain and anxiety in rheumatology patients. Further trials with varying treatment exposures and durations are required to solidify the viability of VR as a treatment option in rheumatology clinics.